Plasma assisted deposition of TaB₂ coatings by magnetron sputtering system - Yakovin, S.; Zykov, A.; Dudin, S.; Farenik, V.; Goncharov, A.; Shelest, I.; Kuznetsov, V. (Вопросы атомной науки и техники, 2017)
In the present paper the results of TaB₂ coating deposition in cluster set-up comprising a low pressure planar magnetron and an inductive plasma source are presented. The system allows to control independently the fluxes of the deposited Ta and B atoms from the sputtered TaB₂ target, and the fluxes of argon ions and electrons from the inductive plasma. Low argon pressure in the chamber allows the deposition process in the collisionless regime, providing the composition of the deposited film which is very close to the stoichiometry of the sputtered target. The correlation of the TaB₂ coating structure with the substrate voltage in the range from -50 to +50 V is demonstrated.